Losartan improves alveolar bone dynamics in normotensive rats but not in hypertensive rats - Mulinari Dos Santos, Gabriel [UNESP]; Dos Santos, Jaqueline Silva [UNESP]; Palin, Letícia Pitol [UNESP]; da SILVA, Ana Cláudia Ervolino [UNESP]; Antoniali, Cristina [UNESP]; Faverani, Leonardo Perez [UNESP]; Okamoto, Roberta [UNESP] (FapUNIFESP (SciELO), 2019)
Hypertension is one of the main causes of premature death in the world; also, it is associated with several bone alterations. Preclinical studies have demonstrated delayed alveolar bone healing in hypertensive rats. However, losartan has been favorable for consolidation of bone grafts and reduction in active periodontitis. Therefore, losartan is suggested to be effective in bone formation stages, as well as in the synthesis of matrix proteins and mineralization. Objectives: To evaluate the alveolar bone dynamics in hypertensive rats treated with losartan by laser confocal microscopy and histological analysis. Methodology: Thirty-two rats, 16 spontaneously hypertensive rats (SHR) and 16 Wistar albinus rats, treated or not with losartan (30 mg/kg/day) were used. Calcein fluorochrome at 21 days and alizarin red fluorochrome at 49 days were injected in rats (both 20 mg/kg). The animals were submitted to euthanasia 67 days after treatment, and then the right maxilla was removed for laser confocal microscopy analysis and the left maxilla for histological analysis. Results: This study showed a greater calcium marking in normotensive animals treated with losartan in relation to the other groups. Laser confocal microscopy parameters showed higher values of bone volume formed, mineralized surface, active surface of mineralization and bone formation rate in normotensive animals treated with losartan. However, a smaller mineralized surface was observed in all hypertensive animals. Conclusion: Losartan can improve bone mineralization parameters under normal physiological conditions, but the same anabolic effect does not occur under hypertension.
Keywords: Bone; Hypertension; Losartan; Spontaneousl y hypertensi ve rats